2010
DOI: 10.1158/0008-5472.can-10-2353
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Expression Identifies Functionally and Molecularly Distinct Tumor-Initiating Cells in Human Glioblastoma Multiforme and Is Required for Gliomagenesis

Abstract: Epidermal growth factor receptor (EGFR) is a known diagnostic and, although controversial, prognostic marker of human glioblastoma multiforme (GBM). However, its functional role and biological significance in GBM remain elusive. Here, we show that multiple GBM cell subpopulations could be purified from the specimens of patients with GBM and from cancer stem cell (CSC) lines based on the expression of EGFR and of other putative CSC markers. All these subpopulations are molecularly and functionally distinct, are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 48 publications
12
164
1
1
Order By: Relevance
“…Because the biological effects driven by estrogen receptor (ER) are directly involved in breast cancer development and progression, 40,41 and epidermal growth factor receptor (EGFR) is overexpressed in CSCs of several tumors, [42][43][44] we asked whether growth factors that were known to contribute to tumorigenesis, such as EGF and 17b-estradiol (E2), mediate their antiapoptotic effects by modulating BAD phosphorylation in CSCs. Although LY294002 significantly reduced the CSC frequency in prostate cancer cells, EGF restored this frequency by protecting from LY-induced apoptosis (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Because the biological effects driven by estrogen receptor (ER) are directly involved in breast cancer development and progression, 40,41 and epidermal growth factor receptor (EGFR) is overexpressed in CSCs of several tumors, [42][43][44] we asked whether growth factors that were known to contribute to tumorigenesis, such as EGF and 17b-estradiol (E2), mediate their antiapoptotic effects by modulating BAD phosphorylation in CSCs. Although LY294002 significantly reduced the CSC frequency in prostate cancer cells, EGF restored this frequency by protecting from LY-induced apoptosis (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…EGFR expression is a marker of proliferating neural stem cells and progenitors (26). Indeed, the presence of the receptor in the membrane marks a highly aggressive subpopulation of GBMCSCs (27) and EGFR signaling has been linked to the expression of stem cell features in GBMs (28). More recently, it has been demonstrated that EGFR is downregulated upon GBM differentiation and that EGFR signaling blockade leads to decreased tumorigenic and stem cell-like potential of GBM neurospheres (29).…”
Section: Discussionmentioning
confidence: 99%
“…CICs were isolated in vitro by the mechanical processing of primary tumor tissues (#1076, 1247, 111011, and 14583) and were cultured in the form of spheres (colon-spheres) in the presence of stem cell-permissive medium (DMEM/F12) containing 20 ng/ml epidermal growth factor and 50 ng/ml fibroblast growth factor 2 (PeproTech, Rocky Hill, NJ), as previously described (17). Part of the primary cell dissociation of CRC tissues was cultured in the presence of RPMI 1640 supplemented with 10% FBS (Biowittaker, Lonza, Treviglio, Italy), hereafter denominated FBS tumor cells (#1076, 1247, 111011, 1039, and 20299), and representing the differentiated tumor cell counterparts, as previously described (10,17,18); these cell lines were used in parallel with CICs.…”
Section: Tissues and Cellsmentioning
confidence: 99%
“…Part of the primary cell dissociation of CRC tissues was cultured in the presence of RPMI 1640 supplemented with 10% FBS (Biowittaker, Lonza, Treviglio, Italy), hereafter denominated FBS tumor cells (#1076, 1247, 111011, 1039, and 20299), and representing the differentiated tumor cell counterparts, as previously described (10,17,18); these cell lines were used in parallel with CICs. Additional CIC lines (#1, 2, and 3) isolated from primary CRC patients have been previously characterized (19).…”
Section: Tissues and Cellsmentioning
confidence: 99%
See 1 more Smart Citation